The Representation of Human Inner Conflict in the Topeng Tarung Dance - Regitha Vidia Pramesti; Agus Budiman; Tatang Taryana (Journal of Dance and Dance Education Studies, 2025)
This study aims to describe the background behind the creation of a dance work that represents the internal conflict of human beings, expressed through choreographic structure, makeup, costume, and musical accompaniment. The research adopts a qualitative paradigm with a descriptive method, using an ethnocoreological approach to analyze both the text and context of Tarung Mask Dance. Data collection methods include observation, interviews, and documentation studies, analyzed using triangulation techniques. The findings reveal that the Tarung Mask Dance is a dance creation rooted in Sundanese traditional patterns. The dance is inspired by the theme of "inner conflict" within the human self, depicting the human struggle against their own nature. The choreography consists of 25 movement variations, predominantly symbolic or meaningful gestures that reflect the inner conflict between two opposing human traits. The makeup used is corrective makeup, which emphasizes facial contours. The costume design is based on the traditional Topeng Priangan attire, preserving the noble elements with glamorous colors while maintaining an elegant appearance. The musical accompaniment uses traditional West Javanese external music, specifically a gamelan set tuned in the pelog scale. Each aspect of the performance illustrates how the conceptual idea of human inner conflict is depicted both textually and contextually.